NOURISHING MINDS: INVESTIGATING THE CONNECTION BETWEEN BREAKFAST HABITS AND ACADEMIC ACHIEVEMENT IN VOCATIONAL NURSING STUDENTS - Kretayuga, Valentino Bayu; Betania, Christina Reni; Dewi, Anastasya Santika; Febriani, Dita Hanna (DPW PPNI Provinsi Jawa Barat, 2024)
Background: Breakfast is one of the internal factors that can affect the learning process and also affect academic achievement. Students who skip breakfast have negative effects such as fatigue, slow reaction time, and cognitive decline. The frequency of breakfast has a significant impact on the physiological health and activation of brain function, which is correlated with academic achievement. Objective: This study aimed to identify the relationship between breakfast habits and academic achievement in second-year vocational nursing students. Methods: This study used cross sectional design. The respondents recruited with a total sampling. Data were collected in November 2021. A total of 45 were participated in this study with inclusion criteria second year students, could fill google form and willing to participated in this study. Results: Eleven students (24%) had breakfast every day. There is no relationship between breakfast habits and academic achievement in second-year vocational nursing students (p > 0.05). But the grade point average is slightly higher in students who take breakfast regularly (mean = 3.50). Conclusion: There is no relationship between breakfast habits and academic achievement in second-year vocational nursing students.